2020
DOI: 10.1108/ijdi-11-2019-0192
|View full text |Cite
|
Sign up to set email alerts
|

Poverty trap in Mexico, 1992-2016

Abstract: Purpose The paper aims to prove that between 1992 and 2016, people in poverty as a proportion of the total population has not been reduced. In particular, food poverty (FP) represented an average of 22%, despite the fact that gross domestic product (GDP) per capita and GDP, social development expenditure and food programme expenditure (both as GDP proportion) grew by 0.96%, 1.9%, 2.7% and −17.4% on an annual average, respectively. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
8
0
2
Order By: Relevance
“…Sin duda, México es el país con más contribuciones en este tema (aunque no son exhaustivas), tanto en trabajos que utilizan métodos paramétricos (Chiquiar, 2005;Carrillo, 2009;Rodríguez, Mendoza, y Venegas, 2015;Mendoza, German, Monfort, y Ordóñez, 2020) como en aquellos que usan herramientas no paramétricas (Aroca, Bosch, y Maloney, 2005;García R. , 2005;Borrayo y Castañeda, 2011;Loría, 2020). En todos ellos, hay diferentes resultados en términos de convergencia, dependiendo del período de análisis.…”
Section: Revisión De Literaturaunclassified
“…Sin duda, México es el país con más contribuciones en este tema (aunque no son exhaustivas), tanto en trabajos que utilizan métodos paramétricos (Chiquiar, 2005;Carrillo, 2009;Rodríguez, Mendoza, y Venegas, 2015;Mendoza, German, Monfort, y Ordóñez, 2020) como en aquellos que usan herramientas no paramétricas (Aroca, Bosch, y Maloney, 2005;García R. , 2005;Borrayo y Castañeda, 2011;Loría, 2020). En todos ellos, hay diferentes resultados en términos de convergencia, dependiendo del período de análisis.…”
Section: Revisión De Literaturaunclassified
“…The relationship between economic growth and poverty reduction is still debated. A few prior studies have found that economic growth influences poverty (Ebunoluwa and Yusuf 2018;Kouadio and Gakpa 2021), while other studies have found that economic growth cannot reduce poverty (Loría 2020;Škare and Družeta 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of the population is around of 67 % living in cities, as a consequence the rural areas have very high poverty levels. Almost 46 % of Mexico population lives below the poverty line, making Mexico rank first in income inequality among the Organisation for Economic Co-operation and Development (OECD) countries ( Iniguez, 2014 ; Iniguez and Kurosaki, 2018 ; Loría, 2020 ; Keeley, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…During 2019, Mexico’s deaths were due to illnesses and health-related problems (88.4 % ), while 11.6 % were due to external causes, such as accidents, homicides, suicides, and others. It should be noted that Mexico‘s deaths due to health problems have three similar causes (both men and women): heart disease (20.7 % ), diabetes mellitus (14 % ), and malignant tumors (11.9 % ) ( Loría, 2020 ).…”
Section: Introductionmentioning
confidence: 99%